Altruism and Christian Love - Browning, Don S. (Zygon, 1992)
Abstract. Sociobiological theories have had little impact on Christian concepts of neighbor love. Since sociobiological theories of altruism depict love as a form of egoistic interest in enhancing one's general fitness, they are often thought to contradict Christian theories of love. However, altruism as defined by sociobiology has more affinity with Roman Catholic views of Christian love as caritas than Protestant views of extreme agape. Sociobiological views of altruism may provide more updated models for defining the orders and priorities of love, which has been an important aspect of Roman Catholic ethics. The family's role in mediating between kin altruism and wider love for the community is investigated.